Experimental study on the human thermal comfort based on the heart rate variability (HRV) analysis under different environments - Zhu, Hui; Wang, Hanqing; Liu, Zhiqiang; Li, Duanru; Kou, Guangxiao; Li, Can (The Science of the total environment, 2018)
In order to study the human thermal comfort under different environments, the electrocardiogram (ECG) data of 6 subjects were recorded continuously under 60 environments composed by different air temperature, relative humidity and air speed that were created by an environmental chamber. Based on the ECG data, the frequency-domain method was adopted to obtain the heart rate variability (HRV) results. Among the HRV indices, the ratio of the low frequency power and high frequency power of the HRV analysis results (LF/HF), which reflects the balance of the autonomic nervous system, was selected as an indicator of the thermal comfort in the study. And the effects of air temperature, relative humidity and air speed on LF/HF were scrutinized. Meanwhile, a questionnaire survey was conducted during the experiment to evaluate the thermal comfort of the subjects. And the relationships between mean LF/HF and thermal sensation, mean thermal comfort were established based on the survey. The results showed that different LF/HF was observed under different environments, and that the air temperature had the most significant effects on LF/HF. The changes in the air temperature could easily lead to the excitation of the sympathetic nerve that could promote the activities of the thermoregulatory effectors thus thermal discomfort. Additionally, the fitting curves illustrating the relationships between LF/HF and thermal sensation and thermal comfort showed that the higher LF/HF yielded thermal discomfort, while the low LF/HF indicated a thermally acceptable state. [Display omitted] •HRV analysis was conducted under 60 different environments.•Subjects had a higher LF/HF when exposed to cold or hot environment.•Only high relative humidity affects LF/HF.•Effects of the air speed on LF/HF depend on the air temperature.•Subjects felt thermally comfortable when LF/HF approximated 1.